Maternal, placental and cord blood cytokines and the risk of adverse birth outcomes among pregnant women infected with Schistosoma japonicum in the Philippines. - Ajibola I Abioye; Emily A McDonald; Sangshin Park; Ayush Joshi; Jonathan D Kurtis; Hannah Wu; Sunthorn Pond-Tor; Surendra Sharma; Jan Ernerudh; Palmera Baltazar; Luz P Acosta; Remigio M Olveda; et al. (PLoS Neglected Tropical Diseases, 2019)
Background The objectives of this study were to 1) evaluate the influence of treatment with praziquantel on the inflammatory milieu in maternal, placental, and cord blood, 2) assess the extent to which proinflammatory signatures in placental and cord blood impacts birth outcomes, and 3) evaluate the impact of other helminths on the inflammatory micro environment. Methods/findings This was a secondary analysis of samples from 369 mother-infant pairs participating in a randomized controlled trial of praziquantel given at 12-16 weeks' gestation. We performed regression analysis to address our study objectives. In maternal peripheral blood, the concentrations of CXCL8, and TNF receptor I and II decreased from 12 to 32 weeks' gestation, while IL-13 increased. Praziquantel treatment did not significantly alter the trajectory of the concentration of any of the cytokines examined. Hookworm infection was associated with elevated placental IL-1, CXCL8 and IFN-γ. The risk of small-for-gestational age increased with elevated IL-6, IL-10, and CXCL8 in cord blood. The risk of prematurity was increased when cord blood sTNFRI and placental IL-5 were elevated. Conclusions Our study suggests that fetal cytokines, which may be related to infectious disease exposures, contribute to poor intrauterine growth. Additionally, hookworm infection influences cytokine concentrations at the maternal-fetal interface. Clinical trial registry number and website ClinicalTrials.gov (NCT00486863).